2015
DOI: 10.1016/j.joca.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage T 1ρ and T 2 relaxation times: longitudinal reproducibility and variations using different coils, MR systems and sites

Abstract: OBJECTIVE To evaluate the longitudinal reproducibility and variations of cartilage T1ρ and T2 measurements using different coils, MR systems and sites. METHODS Single-Site study: Phantom data were collected monthly for up to 29 months on four GE 3T MR systems. Data from phantoms and human subjects were collected on two MR systems using the same model of coil; and were collected on one MR system using two models of coils. Multi-site study: Three participating sites used the same model of MR systems and coils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 32 publications
(29 reference statements)
5
92
1
Order By: Relevance
“…Most important, we used a different sequence and it has to be pointed out that the coil used in this study is a 32‐channel body coil. Li et al recently demonstrated significant variations of T 1 ρ and T 2 values with different coils . Moreover, T 1 ρ values are positively related to the spin‐lock frequency and we used a relatively high spin‐lock frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, we used a different sequence and it has to be pointed out that the coil used in this study is a 32‐channel body coil. Li et al recently demonstrated significant variations of T 1 ρ and T 2 values with different coils . Moreover, T 1 ρ values are positively related to the spin‐lock frequency and we used a relatively high spin‐lock frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The T1 ρ -weighted data set was manually segmented in-house by skilled technicians, with the supervision of radiologists and by using an in-house MATLAB-based program (Mathworks, Natick, Mass), only after they had passed strict training where their segmentations met the metric standard proposed by Carballido-Gamio et al (10) in morphology analysis and the standard of Li et al (19) for relaxation time analysis. The DESS data set was manually segmented; images and segmentation masks are available through the OAI (20).…”
Section: Methodsmentioning
confidence: 99%
“…Both users were trained under the supervision of experienced musculoskeletal radiologists. The procedure for semiautomatic segmentation was evaluated in previous studies reporting processing/reprocessing interobserver intraclass coefficient (ICC) and root mean square / coefficient of variation (RMS‐CV) of the subcompartment T 1ρ quantification equal to 0.961 and 3.9%, respectively, and scan/rescan RMS‐CV of the T 1ρ quantification in compartment equal to 3.1% …”
Section: Methodsmentioning
confidence: 99%